Seroepidemiology and associated risk factors of brucellosis in small ruminants of district Khanewal, Pakistan - Shirwany, Abdul Sammad Ali Khan; Awais, Mian Muhammad; Anwar, Muhammad Irfan; Hameed, Muhammad Raza; Akhtar, Masood; Ijaz, Nabeel; Gill, Shakera Sadiq; Ali, Muhammad Amjad; Bhatti, Muhammad Sibtain; Chaudhry, Mamoona (Journal of Advanced Veterinary and Animal Research, 2024)
Objectives: Keeping in view the economic and veterinary public health importance of brucellosis, this research was conducted to determine its seroprevalence and associated risk determinants in small ruminants in district Khanewal, Southern Punjab, Pakistan. Materials and Methods: Two-stage cluster sampling technique was used for sampling, and the sample size was calculated using C-survey 2.0. Accordingly, sera samples (n = 392) were collected from small ruminants in the study area from October 2022 to July 2023. All the samples were tested for the presence of anti-Brucella antibodies by Rose Bengal Plate Test (RBPT), followed by confirmation of all the samples using an enzyme linked immunosorbent assay (ELISA) kit (ID.vet®, France; sensitivity and specificity=100%, each). Results: The seropositivity rate of brucellosis was 7.14% [n = 28/392; 95% confidence interval (CI) = 4.87%–10.12%] by RBPT, whereas the results of ELISA showed an overall seroprevalence rate of 7.40% (n = 29/392; 95% CI = 5.11%–10.37%) in the study population. Univariate analysis of risk factors revealed that abortion history (AH), retained fetal membranes (RFMs), repeat breeding, flock size (FS), educational status of farmers (ESFs), awareness about brucellosis (AB), and farm hygiene had a significant association with the seroprevalence of brucellosis (p < 0.05). The multivariate analysis using a binary logistic regression model revealed that variables including tehsil, FS, AH, RFM, ESF, AB, and farming system were significant factors (p < 0.05) associated with brucellosis in the target population. Conclusion: Brucellosis is prevalent in small ruminants in Khanewal, Pakistan. The disease burden can be reduced by improving the reproductive health of animals, farm hygiene, and farmers’ awareness about the diseases. Further studies are needed on a larger scale to devise stringent disease control strategies to avoid losses associated with brucellosis at regional, national, and global levels. Adv. Vet. Anim. Res., 11(1): 9-18, March 2024